Developing Constructive and Positive Conflict Resolution Mechanism Strategies at Various Organizational Levels (Global Journal of Human-Social Science, 2020)
The concepts of peace and conflict are inextricably related and exist side by side by the prevailing circumstances. Peace and conflicts have never prevailed at the same moment. Peace exists when there is no conflict while conflict also exists when peace is absent. Peace and conflict as a concept have been the bedrock of peace studies since its emergence as an academic discipline at local, national, and international levels. Therefore a better understanding of the concept of peace and conflict will further widen the horizon of students who want to embark on studies related to the concepts.
Keywords: conflict; culture; dispute; resolution